Contribution of Seagrass Blue Carbon Toward Carbon Neutral Policies in a Touristic and Environmentally-Friendly Island - Bedulli, Camila; Lavery, Paul S.; Harvey, Matt; Duarte, Carlos M.; Serrano, Oscar (Frontiers in Marine Science, 2020)
Estimates of organic carbon (Corg) storage by seagrass meadows which consider inter-habitat variability are essential to understand their potential to sequester carbon dioxide (CO2) and derive robust global and regional estimates of blue carbon storage. In this study, we provide baseline estimates of seagrass extent, and soil Corg stocks and accumulation rates from different seagrass habitats at Rottnest Island (in Amphibolis spp., Posidonia spp., Halophila ovalis and mixed Posidonia/Amphibolis spp. meadows). The Corg stocks in 0.5 m thick seagrass soil deposits, derived from 24 cores, were 5.1+-0.7 kg Corg m-2 (mean+-S.E, ranging from 0.05 to 12.9 kg Corg m-2), accumulating at 23.2+-3.2 g Corg m-2 yr-1 (ranging from 0.22 to 58.9 g Corg m-2 yr-1) over the last decades. There were significant differences in Corg content (%) and stocks (mg Corg cm-3), stable carbon isotope composition of the soil organic matter (d13C) and soil grain size among the seagrass meadows studied, highlighting that biotic and abiotic factors influence seagrass soil Corg storage. Mixed meadows of Posidonia/Amphibolis spp. and monospecific meadows of Posidonia spp. and Amphibolis spp. had the highest Corg stocks (ranging from 6.2 to 6.4 kg Corg m-2), while Halophila spp. meadows had the lowest Corg stocks (1.2+-0.6 kg Corg m-2). We estimated a total soil Corg stock of 48.1±8.5 Gg Corg beneath the 755 ha of Rottnest Island’s seagrasses, and a Corg sequestration capacity of 0.81+-0.06 Gg Corg yr-1, which is equivalent to the sequestration of ~22% of the island’s current annual CO2 emissions. Our results contribute to the existing global dataset on seagrass soil Corg storage and show a significant potential of seagrass to sequester CO2, which are particularly relevant in the context of achieving carbon neutrality through conservation actions in environmentally-marketed, tourist destinations such as Rottnest Island.